2020
DOI: 10.1002/anie.202003676
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Peptide Synthesis Enabled by a Transient Protecting Group

Abstract: The growing interest in synthetic peptides has prompted the development of viable methods for their sustainable production. Currently, large amounts of toxic solvents are required for peptide assembly from protected building blocks, and switching to water as a reaction medium remains a major hurdle in peptide chemistry. We report an aqueous solid‐phase peptide synthesis strategy that is based on a water‐compatible 2,7‐disulfo‐9‐fluorenylmethoxycarbonyl (Smoc) protecting group. This approach enables peptide ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…6). 95,96 The Fmoc-analogue Smoc is removed under basic conditions (e.g. aqueous ammonia, ethanolamine or ethylenediamine, or piperidine), whereas the SBoc, tBuS, StBuS, sulfo-Trt and BOMS are removed under acidic conditions (e.g.…”
Section: Water-based Sppsmentioning
confidence: 99%
See 3 more Smart Citations
“…6). 95,96 The Fmoc-analogue Smoc is removed under basic conditions (e.g. aqueous ammonia, ethanolamine or ethylenediamine, or piperidine), whereas the SBoc, tBuS, StBuS, sulfo-Trt and BOMS are removed under acidic conditions (e.g.…”
Section: Water-based Sppsmentioning
confidence: 99%
“…Furthermore, they determined epimerisation to be <0.5% for most studied amino acids in model peptides (up to 2% for Asp/Asn) and showed that side reactions such as aspartimide formation were sequence and temperature dependent. 96 Overall, ASPPS is an interesting technology which requires further development. It is currently not clear if the approach would be generally successful when applied to longer and more complex peptide sequences.…”
Section: Water-based Sppsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further improve the properties of water‐compatible protecting groups, SO 3 − ‐functionalized protecting groups, so‐called 9‐(2‐sulfo)fluorenylmethyloxycarbonyl (Smoc) amino acid derivatives, [ 116 ] as well as additional solvation strategies, additional compatible activators and microwave irradiation were successfully implemented. [ 108,117–123 ]…”
Section: Related Research Areas and Future Directionsmentioning
confidence: 99%